PERAN LPTK DALAM MENYIAPKAN TENAGA GURU SMK BIDANG AGRIBISNIS - Mukhidin Mukhidin; Dartum Dartum (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThe role of LPTK of High School Vocational Teacher of agribusiness field should be restructured theeducational system and the curriculum offerings in agribusiness field. The reforms are also needed in assessmentof needs analysis and broader cooperation. The LPTK should be able to redesign the curriculum of high schoolvocational teacher’s candidate of agribusiness field related to the needs and development of agribusiness fieldand should be as the facilitator and mediator on the variety of agribusiness activity for the candidate and alsoHigh School Vocational Teacher of agribusiness field. Some of the approach that should be reviewed by LPTKshould refer to the analysis result of the Ministry of Agriculture is aimed to the development of curriculum design,implementation model and the evaluation. Besides that the role of LPTK need to access the agribusiness curriculummaterials as outlined in the course of Agribusiness. The High School Vocational Teacher in Agribusiness fields areplay the strategic roles, the especially in shaping the entrepreneurial spirit in agribusiness fields and develop acomprehensive network of agribusiness and develop the potential of learners. Thus the LPTK roles are very essentialin printing the educators, particularly vocational teacher candidates’ agribusiness.Keywords: Agribusiness, High School Vocational Teacher of Agribusiness Field, LPTK